Production of heterogeneous catalyst for biodiesel synthesis - shah, beenish; Sulaiman, Sarina; Jamal, Parveen (2014)
The waste food material namely crab shell, egg shell and fish bone is screened for biodiesel synthesis by tranesterification reaction to determine the source providing the highest biodiesel yield. The solid oxide materials were calcined at 900°C at 2-4hrs to convert CaCO3 to CaO species. Tranesesterification is carried out at 65°C for 4 hrs with varied methanol to oil ratio. It was found that although egg shell, and crab shell gave average biodiesel yields, fish bone provided outstanding results of the three catalysts. This research signifies successful application of waste resources as an emerging prospective for economical preparation of heterogeneous catalyst, developing an unconventional avenue for reusing of this solid waste.